2004
DOI: 10.1177/0363546503261724
|View full text |Cite
|
Sign up to set email alerts
|

Injury Mechanisms for Anterior Cruciate Ligament Injuries in Team Handball

Abstract: The injury mechanism for anterior cruciate ligament injuries in female team handball appeared to be a forceful valgus collapse with the knee close to full extension combined with external or internal rotation of the tibia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
1,060
1
34

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,073 publications
(1,134 citation statements)
references
References 31 publications
39
1,060
1
34
Order By: Relevance
“…Recent studies have shown gender differences in lower-extremity kinematics and kinetics in athletic tasks [1,2]. Numerous authors have identified valgus collapse of the knee as the common body position in noncontact ACL injuries [26][27][28]. Core stability may also be a factor in ACL injury [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown gender differences in lower-extremity kinematics and kinetics in athletic tasks [1,2]. Numerous authors have identified valgus collapse of the knee as the common body position in noncontact ACL injuries [26][27][28]. Core stability may also be a factor in ACL injury [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, injury mechanisms should be investigated less arbitrarily, for example using video analysis which has been done recently in other team sports such as basketball and team handball [28,35].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Non-contact ACL injuries appear to occur most commonly during landing (Hume and Steele 1997;Otago and Neal 1997), rapid change of direction (Bartold 1997) and deceleration (Miller, Cooper, and Warner 1995). Furthermore, most non-contact ACL injuries appear to occur close to foot strike with the knee close to full extension and in a valgus position (Boden, Dean, Faegin, et al 2000;Olsen, Mykelbust, Engebretsen, et al 2004). Not surprisingly, the incidence of ACL injury is relatively high in sports involving a high frequency of landing, decelerating and rapid changes of direction such as basketball, netball, handball and volleyball (Arendt and Dick, 1995;Griffin, Angel, Albohm, et al 2000).…”
Section: Introductionmentioning
confidence: 99%